2019
DOI: 10.1111/nph.15877
|View full text |Cite
|
Sign up to set email alerts
|

A role for the auxin precursor anthranilic acid in root gravitropism via regulation of PINFORMED protein polarity and relocalisation in Arabidopsis

Abstract: Summary distribution of auxin within plant tissues is of great importance for developmental plasticity, including root gravitropic growth. Auxin flow is directed by the subcellular polar distribution and dynamic relocalisation of auxin transporters such as the PIN‐FORMED (PIN) efflux carriers, which can be influenced by the main natural plant auxin indole‐3‐acetic acid (IAA). Anthranilic acid (AA) is an important early precursor of IAA and previously published studies with AA analogues have suggested that AA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…1a). The PINs have been found to conducive to nearly every step of auxin uxes [3,18,35,20] and the auxin distribution patterns have been predicted and explained through auxin transport [2,6,1]. In this study, the expression of PgPIN1 and PgPIN10 showed higher in LBS than TSH (Fig.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…1a). The PINs have been found to conducive to nearly every step of auxin uxes [3,18,35,20] and the auxin distribution patterns have been predicted and explained through auxin transport [2,6,1]. In this study, the expression of PgPIN1 and PgPIN10 showed higher in LBS than TSH (Fig.…”
Section: Resultssupporting
confidence: 51%
“…The PINs have been found to conducive to nearly every step of auxin uxes [3,18,35,20] and the auxin distribution patterns have been predicted and explained through auxin transport [2,6,1]. FLP and MYB88 have been found to can regulate root gravitropism [27], the late stages of stomatal development [11], cold hardiness [30], female reproductive development [17], and guard mother cell proliferation [11,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzenoids accumulated at different time-points in M. oryzae-infected transgenic rice, in which salicylic acid and anthranilic acid (Vitamin L1) accumulated at three-time points. Anthranilic acid (AA) is a vital precursor in the synthesis of major auxin, indole-3-acetic acid (IAA) [24], essential for maintaining the growth of infected transgenic rice. While salicylic acid plays a vital role in defense response [25], suggesting that MoSDT1 may play a role in balancing rice growth and defenses.…”
Section: Oryzae-infected Mosdt1-transgenic Rice Showed Accumulatiomentioning
confidence: 99%
“…Firstly, rice leaves were inoculated with spores of M. oryzae strain 95234I-1b, and then sprayed with exogenous compounds after 72 h at three concentrations (Supplementary Table 2), and the concentrations of six compounds were prepared [21,24,26]. Disease index =∑ (number of leaves at each grade × representative values at all grades)/(review total leaf number × highest grade representative value)×100 [18].…”
Section: Evaluation Of Exogenous Compound Treatment On Rice Resistancementioning
confidence: 99%